Collaboration of Teachers, Parents, and Communities in Educational Innovation - Nurhaswinda, Nurhaswinda; Arrobbi, Restu; Ramadhani, Nada Nadhiroh; Sabani, Yolita; Ahyar, Mutia Saqillah; Afifah, Rifdah; Fahrezi, Riko; Wulandari, Wulandari; Zahera, Ulfa; Alfarizi, Ahmad Rafid; Sari, Widya Puspita; Yosa, Rayhan Putra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to examine the role of collaboration between teachers, parents, and communities in creating effective and relevant educational innovations in schools. In the era of globalization and rapid technological advancements, the challenges in education have become more complex and require collective efforts from various stakeholders. This research adopts a qualitative approach with a case study design in several schools that have successfully implemented a collaborative model involving teachers, parents, and communities in developing educational innovations. Data were collected through in-depth interviews with teachers, parents, and community leaders, participatory observations, and document studies. Thematic analysis was used to identify key themes related to the dynamics of this collaboration. The findings reveal that strong collaboration can enhance the quality of learning, strengthen parental involvement in the educational process, and create an environment that supports the holistic development of students. Key success factors include open communication, shared understanding of educational goals, and the utilization of local resources. However, the main challenges faced are time constraints, differing perceptions of each party’s role, and limited digital literacy among parents. The results of this study are expected to provide insights for policymakers and education practitioners in designing more effective strategies to strengthen collaboration in order to improve the quality of education.